Historical Notes on the Emergence and Development of the Physiological Sciences Society in Cienfuegos - María de Jesús Sánchez Bouza; Pedro Sánchez Frenes; Amarilis Chaviano Díaz; Liliam Leguén Gulgar (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2017)
The development achieved by the scientific activity in the public health field, during the revolutionary period, promoted the origin of subsidiaries of scientific societies in different provinces of the country. In Cienfuegos the different medical specialties started to form their own chapters, among them, the Physiological Sciences. This paper is aimed at exposing the collected information about the emergence and development of the Scientific Society in Cienfuegos. A bibliographical review was realized and written testimonial sources were used (documents linked to the functioning of the mentioned organ). Elements related to the society, from its first Board of Directors, the main evidences found in scientific activities developed from its foundation, until its main contributions to the scientific work of the province.